2019
DOI: 10.1039/c9nj03394g
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine and amide-ornamented dihydropyridinesviaa molecular hybridization approach: design, synthesis, biological evaluation and molecular docking studies

Abstract: A series of novel phenothiazinyldihydropyridine dicarboxamides 7a–7j was synthesized by adopting a multi-step synthetic strategy and characterized through physical and spectral techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Phenothiazine, a fused tricyclic aromatic entity with nitrogen and sulfur heteroatoms in the middle six-membered ring, is one of the important structural units existing in a diverse range of bio-pertinent chemical entities and sensitizers. In continuation of our endeavors on methodology development and the synthesis of heterocyclic molecules, [63,[65][66][67][68][69][70] we initially synthesized phenothiazinylmethylenemalononitrile 4a from its corresponding phenothiazine-based carbaldehyde precursor 2a, synthesized from commercially available 10Hphenothiazine through hexylation followed by condensation and formylation (Vilsmeier-Haack reaction) strategies, and malononitrile with the use of sodium ethoxide in ethanol in order for its cytotoxicity evaluation against pancreatic cancer cells (Figure 8). Further, this chemical entity would act as an efficient intermediate for the development of potent biological agents as well, as various functionalization can be possible around the phenothiazine nucleus and nitrile functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…Phenothiazine, a fused tricyclic aromatic entity with nitrogen and sulfur heteroatoms in the middle six-membered ring, is one of the important structural units existing in a diverse range of bio-pertinent chemical entities and sensitizers. In continuation of our endeavors on methodology development and the synthesis of heterocyclic molecules, [63,[65][66][67][68][69][70] we initially synthesized phenothiazinylmethylenemalononitrile 4a from its corresponding phenothiazine-based carbaldehyde precursor 2a, synthesized from commercially available 10Hphenothiazine through hexylation followed by condensation and formylation (Vilsmeier-Haack reaction) strategies, and malononitrile with the use of sodium ethoxide in ethanol in order for its cytotoxicity evaluation against pancreatic cancer cells (Figure 8). Further, this chemical entity would act as an efficient intermediate for the development of potent biological agents as well, as various functionalization can be possible around the phenothiazine nucleus and nitrile functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the radical scavenging activity by a DPPH assay showed that bromo and fluoro atoms in ortho position or an m -nitro on the aryl ring influences this antioxidant effect. In fact, the hybrids 24b , 24c and 24d act as antioxidants with an activity comparable to the standard, i.e., ascorbic acid [ 49 ].…”
Section: Anticancer Hybridsmentioning
confidence: 99%
“…Interestingly, compounds 24b and 24d – h showed a high effect (near 100%) when compared with the standard drug. An increase in the anti-inflammatory activity was observed in molecules with more electronegative groups in the amide phenyl group [ 49 ]. Of these, compound 24d , bearing a fluoro in the ortho -position, presented the most potent activity [ 49 ].…”
Section: Analgesic and Anti-inflammatory Propertiesmentioning
confidence: 99%
“…Molecular dynamics studies were conducted on B-cell lymphoma and B-cell lymphoma, and revealed a promising binding affinity in docking (8.10 kcal mol) ( Scheme 58 ). 88 Singh et al (2014) developed and synthesized novel nitrogen mustard pharmacophore hybrids such as DHP-M 58A without a spacer and DHP-L-M 58B with an ethyl spacer. They were evaluated in vitro for their cytotoxicity properties against the COLO 205 (colon), A 549 (lung), IMR-32 (neuroblastoma) and U 87 (glioblastoma) cancer cell lines by MTT assay with chlorambucil and docetaxel standard drugs.…”
Section: Synthetic Advancesmentioning
confidence: 99%